2019
DOI: 10.3390/nu11020285
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell Concentration on the Persistence in the Human Intestine of Four Probiotic Strains Administered through a Multispecies Formulation

Abstract: Studies devoted to evaluating the outcome of different doses of probiotics are very limited, especially for multistrain formulations. In this context, we performed an intervention study that aimed to compare the effect of the administration of two doses (7 billion and 70 billion bacterial cells) of a multistrain probiotic formulation on the persistence of the four probiotic strains that were present in the product in the fecal samples collected from healthy subjects. The overall persistence of the probiotic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 25 publications
(25 reference statements)
2
32
1
Order By: Relevance
“…All three other microbes were significantly increased in their levels with both low and high dose simulations, which is in agreement with earlier observations [3,17]. The increase in the counts was dose dependent, with the counts in the higher dose simulations being more than one log10 higher than in the lower dose simulations, in agreement with a recent human intervention study on the same probiotic product [5].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…All three other microbes were significantly increased in their levels with both low and high dose simulations, which is in agreement with earlier observations [3,17]. The increase in the counts was dose dependent, with the counts in the higher dose simulations being more than one log10 higher than in the lower dose simulations, in agreement with a recent human intervention study on the same probiotic product [5].…”
Section: Discussionsupporting
confidence: 91%
“…While the evidence for this general conclusion is limited and would benefit from further research, it appears that for antibiotic-associated diarrhea, higher doses are more efficacious [4]. Further, the recovery of higher levels of fed probiotics from feces typically results from the consumption of higher doses [4,5]. In addition to higher counts, there is also a marketing trend to include a higher number of strains in probiotic formulations [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have used quantitative strain-specific qPCR analyses to monitor the transit of supplemented bacterial strains, most of which focusing on single probiotic strains (Tuohy et al 2007;Ahlroos and Tynkkynen 2009;Nagulesapillai et al 2017;Arioli et al 2018;Radicioni et al 2019). However, a study using a 4-strain blend administered at a low (seven billion CFU) and high dose (70 billion CFU) reported results consistent with ours; they observed a longer post-intervention persistence with the higher supplement dose (70 billion CFU) for three out of the four supplemented strains (Taverniti et al 2019). In our study, persistence, which was assessed once after a 7-day washout period, was observed in more participants at the 25B dose than in the 5B dose.…”
Section: Discussionsupporting
confidence: 87%
“…Nevertheless, even if the identification of a "healthy" microbial signature remains elusive, the need for evaluating the safety and understanding the effects of specific probiotic formulations on intestinal microbiota profile commands for an assessment in a general population of adults without known dysbiosis-associated diseases. Few studies in humans have evaluated the individual behavior of several bacterial strains ingested simultaneously in terms of microbiota contribution and intestinal persistence after ingestion (Mennini et al 2019;Taverniti et al 2019). Therefore, conducting more studies in various samples of the general population is essential to gather insight into individual strain characteristics when administered within probiotic blends, such as persistence, as well as to refine our general understanding of emerging concepts about microbiota functional composition, such the significance of the Firmicutes-Bacteroidetes (FB) ratio in non-diseased individuals.…”
Section: Introductionmentioning
confidence: 99%